Wage Dynamics and Unobserved Heterogeneity : Time Preference or Learning Ability? - Lalith Munasinghe; Nachum Sicherman (Institute for the Study of Labor (IZA), 2004)
A large fraction of the variation in wage levels and wage growth rates among individuals remains unexplained. Economists argue that ?unobserved? heterogeneity is among the more likely reasons for this unexplained variation in wages. The source of individual heterogeneity is typically attributed to data limitations and the unobservability of certain productivity related factors. In this paper we present a theory of career choice and derive a discriminating test between two inherently unobservable sources of heterogeneity – learning ability and workers? inter-temporal preferences (discounting) – both of which can clearly account for the variation in wage levels and wage growth rates. We apply this test to the large observed differences in wages and wage growth rates between smokers and non-smokers. The empirical evidence suggests that smoking is a proxy for individual discount rates.
Keywords: J31; J24; J22; 330; wage dynamics; unobserved heterogeneity; discount rates; learning ability; Lohnstruktur; Zeitpräferenz; Abzinsung; Lernen; Rauchen; Schätzung; Vereinigte Staaten